A low cost nutrient formulation with a buffer for simplified hydroponics systems - Saparamadu, J.S.; Wijesekera, R.D.; Gunawardhana, H.D.; Weerakkody, W.A.P. (My University, 2010)
The pH of the nutrient solution is a major determinant of nutrient uptake by the plants. The most suitable pH range for the plants is recognized as 5.8 - 6.5. Therefore, the pH of the nutrient solution has been adjusted to this range before application, using a pH meter. Further more, the pH of the root solution might change with time after application due to many factors and it is not practical to adjust the pH of the root solution homogeneously in a aggregate type hydroponics plant bed. These problems can be overcome by incorporating a buffer system into the nutrient formulation. A new nutrient formulation with a buffer (NF) was designed and prepared using commercial grade compounds. The buffer system HPO4 2-/ H2PO4 - was prepared using KOH and H3PO4 which are also used as sources of K and P in the nutrient formulation. Therefore, no additional cost was incurred due to the buffer system. The buffer capacity was determined as 4 mmol / dm3. The success of the buffer was evaluated by measuring its ability to withstand pH changes in the plant bed. A field trial was carried out with the formulation NF and commercially available nutrient pack (Al) which does not incorporate a buffer, for tomato and bean plants in a simplified hydroponics system under external environmental conditions. The pH of the solutions in plant beds was measured daily during the first two weeks after transplanting/sowing. The overall pH change in the root solution, two weeks after transplanting (compared to the pH of the solution applied), was less when the tomato and bean plant beds were treated with NF than with Al. This can be attributed to the buffering action of the HPO4 2-/ H2PO4 - buffer system in the NF formulation. Since commercial grade chemicals are used to prepare the pack, the cost of the pack is very much less than similar packs available in the market.